Romania, Development and European Integration in the Context of the Implementation of the European Union Strategy for the Danube Region: Array - Ene, Angela-Mihaela (Journal of Danubian Studies and Research, 2020)
Romania, the initiating country of the European Union Strategy for the Danube Region, along with Austria, has the opportunity, at least for the Danube basin, to make substantial and much more productive progress in its regional development. Our approach is that this strategy represents a mechanism for transnational development and can generate a more than necessary stimulus in achieving the general objectives that Romania has proposed in the process of economic and social cohesion for the integration in the European Union. In the content of this approach, we will try to emphasize Romania’s major role in stimulating the vitality and the force of a macro-program of development, a macro-program that Romania has the chance to capitalize in its favor, but also to demonstrate its capacity as a driving force in the Union’s South - East region. Considering that Romania exerts its presidency of the Strategy from 1st November 2018 to 30th October 2019, represents a very important asset for developing and canalizing this funding mechanism towards a very important national interest.